Pre-hospital emergency medical services: a population based study of pediatric utilization. Issue 4 (1st December 1999) - Suruda, Anthony; Vernon, Donald D; Reading, James; Cook, Larry; Nechodom, Patricia; Leonard, Daniel; Dean, J Michael
Abstract : Objectives —To examine emergency medical services (EMS) usage by children in one state. Methods— Dispatch of an EMS vehicle in response to a call in the US is referred to as a "run". Runs for Utah for 1991–92 were linked to corresponding hospital records. Abbreviated injury severity scores (AISs) were assigned using ICDMAP-90 software. Results— For the two year period there were at least 15 EMS runs per 100 children per year, with incomplete reporting from rural areas. EMS response and scene times were similar for all age groups, but interventions were less frequent for children under 5 years of age. When the principal AIS region of injury was the head, neck, or face, cervical immobilization was less frequent for children less than 5 years of age (54%) than for older children (76%) and immobilization was associated with improved outcome, using the crude measure of lower hospital charges. There was a similar association between splinting of upper extremity fractures and reduced hospital charges. Both associations did not appear to be due to differences in injury severity. Conclusions— The majority of EMS use by children is for trauma. Children less than 5 years of age are less likely to have an EMS intervention than older children. Whether the lower frequency of interventions is due to the lack of properly sized equipment on the vehicle, or to other factors, is undetermined.